2009
DOI: 10.4012/dmj.28.153
|View full text |Cite
|
Sign up to set email alerts
|

Combination with allogenic bone reduces early absorption of .BETA.-tricalcium phosphate (.BETA.-TCP) and enhances the role as a bone regeneration scaffold. Experimental animal study in rat mandibular bone defects

Abstract: β-tricalcium phosphate (β-TCP) was grafted into rat mandibular bone defects to assess its potential as a scaffold material for bone regeneration. For this purpose, β-TCP (TCP), allogenic bone (Allograft), and allogenic bone combined with β-TCP (Combined) were employed as graft materials. To the left side of the graft materials in the bone defects, platelet-rich plasma (PRP) was added. The rats were sacrificed at one, three, and five weeks. Bone formation rate (BFR), remaining β-TCP rate (RTR), β-TCP absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…The rat mandibular bone defect model was developed to study bone formation in the mandible [89]. This model has been useful in designing studies to compare the efficacy of different materials to augment bone formation including barrier membranes [90–92], bone grafts [93], growth factors and hormones [92, 9496] and other factors such as ultrasound stimulation [97, 98]. In this model, the angle of the rat mandible is surgically exposed on both the buccal and the lingual aspects and a through-and-through osseous defect of 5 mm is created with a trephine burr.…”
Section: Rat Mandibular Critical Size Defectmentioning
confidence: 99%
“…The rat mandibular bone defect model was developed to study bone formation in the mandible [89]. This model has been useful in designing studies to compare the efficacy of different materials to augment bone formation including barrier membranes [90–92], bone grafts [93], growth factors and hormones [92, 9496] and other factors such as ultrasound stimulation [97, 98]. In this model, the angle of the rat mandible is surgically exposed on both the buccal and the lingual aspects and a through-and-through osseous defect of 5 mm is created with a trephine burr.…”
Section: Rat Mandibular Critical Size Defectmentioning
confidence: 99%
“…In relation to the β-TCP (Bionnovation), no report in the literature was found. Nevertheless, in general, β-TCP has been widely studied and it has been considered a biocompatible, osteoconductive, and resorbable bone substitute (Al-Sanabani et al, 2013;Hirota et al, 2009;Shiratori et al, 2005). Tests of biocompatibility indicated that the experimental β-TCP, as well as both β-TCP and Bio-Oss ® , exhibited neither cytotoxicity nor genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that α-TCP particles present cytotoxicity (Santos et al, 2002) and instability (Lew, Othman, Ishikawa, & Yeoh, 2012). On the other hand, β-TCP has been considered biocompatible, absorbable and osteoconductive, leading to formation of bone tissue around and also inside pores (Al-Sanabani et al, 2013;Hirota et al, 2009). It has been used in a variety of surgical procedures with satisfactory clinical and histological findings in animals and humans (Al-Sanabani et al, 2013;Brkovic et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Bone tissue is constantly replaced by osteoblasts and osteoclasts. Osteoprotegerin (OPG) inhibits osteoclast differentiation, whereas the receptor activator of NF-kappa B ligand (RANKL) enhances its differentiation and the solubility of β-TCP was influenced by these cells function 2,8) .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, β-tricalcium phosphate (β-TCP)-based bone substitutes were developed [2][3][4][5] . β-TCP often shows early absorption before adequate bone replacement has occurred.…”
Section: Introductionmentioning
confidence: 99%